THE EFFECT OF PROFITABILITY, ASSET GROWTH AND SALES GROWTH ON CAPITAL STRUCTURE IN MANUFACTURING COMPANIES IN THE SUB-SECTOR COSMETICS AND HOUSEHOLD LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2019-2023 - Arsya Ardana; Jummaini; Rico Nur Ilham; Ghazali Syamni (CV. Radja Publika, 2026)
This study aims to examine the effect of profitability, asset growth, and sales growth on capital structure in Cosmetics and Household sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The capital structure in this study is proxied by the Debt to Asset Ratio (DAR), profitability is proxied by Return on Assets (ROA), asset growth is proxied by asset growth (AG) and sales growth is proxied by sales growth (SG). The data collection technique uses secondary data in the form of financial reports accessed from the official website www.idx.co.id and also from the website of each company. The sample used in this study is a cosmetics and household company listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample selection used a purposive sampling technique with a population of 7 companies and a sample of 6 companies according to the established criteria. Then the data that has been collected is then processed using eviews, the data analysis method used in this study is panel data regression analysis. The results of the study indicate that profitability has a negative and significant effect on capital structure, asset growth has a negative and significant effect on capital structure, while sales growth has a positive but insignificant effect on capital structure in cosmetics and household companies listed on the Indonesia Stock Exchange for the period 2019-2023. Further research can consider the influence of these variables and expand the scope of research to other industrial sectors. The results of this study not only provide new insights into the financial management situation in companies, but can also be a basis for further refining and developing existing theories.